Quem é mais importante? A avaliação do bem-estar humano no manejo florestal sustentável - Colfer, C.J.P.; Prabhu, Ravi; Günter, M.; McDougall, C.; Porro, N.M.; Porro, R. (Center for International Forestry Research, 2000)
Who counts most? Assessing human well being in sustainable forest management presents a tool, 'the Who Counts Matrix', for differentiating 'forest actors', or people whose well-being and forest management are intimately intertwined, from other stakeholders. The authors argue for focusing formal attention on forest actors in efforts to develop sustainable forest management. They suggest seven dimensions by which forest actors can be differentiated from other stakeholders, and a simple scoring technique for use by formal managers in determining whose well being must form an integral part of sustainable forest management in a given locale. Building on the work carried out by the Center for International Forestry Research on criteria and indicators, they present three illustrative sets of stakeholders, from Indonesia, Côte d'Ivoire and the United States, and Who Counts Matrices from seven trials, in an appendix.